Seroprevalencia de paratuberculosis bovina en rodeos de cría y de leche de dos departamentos de la provincia de Santa Fe (Argentina) - Abdala, A. (2019)
Paratuberculosis (PTB) is a granulomatous chronic disease of the gastrointestinal tract of domestic and wild ruminants, caused by Mycobacterium avium subsp. paratuberculosis (MAP). The disease has been identified previously in dairy and beef cattle herds of Argentina, however the prevalence estimates are scarce. To characterize the PTB situation in both cattle production system of Santa Fe province, the serological prevalence in dairy and beef cattle herds was determined through a commercial ELISA. The study was carried on Castellanos and San Cristobal departments that include a significant proportion of the provincial cattle that produce milk and meat, respectively. Seventy herds were studied for each productive system, with a minimum of 20 cows sampled per herd. PTB prevalence at the herd and bovines level was 35.6% and 2.1% for dairy cattle and 66% and 9% for beef cattle respectively. Unexpectedly, the meat production systems showed higher prevalence than dairy systems. These results strongly suggest that Argentina should implement an official PTB control program that include particularly breeder cabins, to preclude its spread with livestock movement.